ASSESSING WATER REDUCTION DYNAMICS IN THE CHAI RIVER, DAKUK, IRAQ USING REMOTE SENSING AND GIS TOOLS - Zainab Omran Abdulrahan; Qahtan A.M. AL Nuaimy; Mustafa Ridha Mezaal (Western European Studies, 2025)
Water erosion is a major environmental issue in the globe today, contributing to sedimentation and degrading agricultural lands. The study objectiveis to probe the dynamics of water erosion in the Chai River basin, Dakuk, Iraq. Geographic Information System (GIS) and remote sensing are genuinely employed to detect and quantitative the changes in water of Chai River relative to barren and vegetation features. Maximum Likelihood classification method is applied to classify the Sentinel Satellite images from 2015 to 2014. Change detection analysis is employed to detect the changes in landcover classes between the selected years. The results were revealing that soil dominated the landscape in 2015, followed by water and plants. By 2024, the water class expanded, reaching 3.7559 km², primarily at the expense of soil. The study found that 2.0445 km² of soil was converted to water and plants, indicating a decrease in soil cover. The water class gained 1.3800 km², while vegetation remained stable. This suggests potential hydrological or environmental changes. Because the sand class side of the river increased because of the recent decline in rainfall rates, the boundaries Chai River and water level dropped between 2015 and 2024.
Keywords: Change detection; GIS; Remote sensing